2020
DOI: 10.17583/rasp.2020.5538
|View full text |Cite
|
Sign up to set email alerts
|

“This Brings you to Life” The Impact of Friendship on Health and Well-being in Old Age: the Case of La Verneda Learning Community

Abstract: Friendship has been studied along centuries, since ancient times to present-day, as the basis of the social cornerstone, present at all stages of the lifespan and belonging to the world of truthful sentiments. Benefits of friendship on health have been demonstrated. Less is known about the role of friendship on seniors. The aim of this case study has been to show how the end friendship developed in an adults’ school operating for more than 40 years in Barcelona is having a positive impact on the well-being and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous literature has already pointed out the benefits of dialogic learning in both instrumental knowledge (Flecha & Soler, 2013) and values, feelings and relationships (León-Jiménez et al, 2020). Moreover, in the case of the adult school, it must be added that dialogical spaces such as the gatherings promote wellbeing and friendship among older people (León-Jiménez, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has already pointed out the benefits of dialogic learning in both instrumental knowledge (Flecha & Soler, 2013) and values, feelings and relationships (León-Jiménez et al, 2020). Moreover, in the case of the adult school, it must be added that dialogical spaces such as the gatherings promote wellbeing and friendship among older people (León-Jiménez, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (Serrano, 2015 ; Aubert et al, 2016 ; León-Jiménez, 2020 ), the key to its success is an effective democratic organisation and functioning, developing a wide variety of activities and an accessible timetable. Adult participants, together with teachers and volunteers, decide and organise the activities to be carried out in the school according to their needs and interests.…”
Section: Resultsmentioning
confidence: 99%
“…At this particular point, social support manifested in values such as solidarity and friendship has already been shown to play a key role in overcoming the challenges of current society (Anderson and Fowers 2020;García-Yeste et al 2020;Giner 2011;Leon-Jimenez 2020;Merodio et al 2020;Umberson et al 2010). Although such values have been widely demonstrated to have a positive impact in a range of social spheres and in terms of wellbeing, postmodern discourse has actively argued how useless love, kindness, and solidarity are in response to current daily life challenges (Hooks 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, research has widely demonstrated how actions grounded in values such as love, friendship, or solidarity have the potential to enhance social cohesion; to provide emotional, economic, or other kinds of support; and to promote health and the public good (Gill 2020;Leon-Jimenez 2020). At the individual level, neuroscience has also evidenced how kindness fosters a healthy brain (Galante et al 2014) and leads to relationships characterized by pleasure and desire (Racionero-Plaza et al 2020).…”
Section: Introductionmentioning
confidence: 99%